Characterization of neurotransmitters and related metabolites in Daphnia magna juveniles deficient in serotonin and exposed to neuroactive chemicals that affect its behavior: A targeted LC-MS/MS method. (January 2021) - Fuertes, Inmaculada; Barata, Carlos
Abstract: Neurotransmitters are endogenous metabolites that play a crucial role within an organism, at the chemical synapses. There is a growing interest in their analytical determination for understanding the neurotoxic effect of contaminants. Daphnia magna represents an excellent aquatic model for these environmental studies, due to its similarities with vertebrates in several neurotransmitters and related gene pathways and because of its wide application in ecotoxicological studies. Within this study, an accurate and sensible method of analysis of 17 neurotransmitters and related precursors and metabolites was developed. The method was validated in terms of sensitivity, reproducibility, precision, and accuracy, and also matrix effect was evaluated. As an independent probe of method validation and applicability, the method was applied to two different scenarios. First, it was used for the study of neurotransmitter levels in genetically mutated tryptophan hydrolase D. magna clones, confirming the absence of serotonin and its metabolite 5-HIAA. Additionally, the method was applied for determining the effects of chemical compounds known to affect different neurotransmitter systems and to alter Daphnia behavior. Significant changes were observed in 13 of the analyzed neurotransmitters across treatments, which were related to the neurotransmitter systems described as being affected by these neurochemicals. These two studies, which provide results on the ways in which the neurotransmitter systems in D. magna are affected, have corroborated the applicability of the presented method, of great importance due to the suitability of this organism for environmental neurotoxicity studies. Graphical abstract: Image 1 Highlights: Neurotransmitter metabolites in Daphnia magna were determined by a targeted LC-MS/MS, determining up to 17 metabolites belonging to five different neurotransmitter systems. The method was validated using animals deficient in serotonin and neuroactive compounds. Knockout animals for tryptophan hydrolase gene showed low levels of serotonin related metabolites. The 12 tested neuroactive substances affected behavioral escape responses to light. Up to 13 metabolites were affected by the studied compounds in an expected way.